Ovipositional behavior in predator and prey blowflies - Giao, Juliana Zibordi; Conde Godoy, Wesley Augusto (Springer, 2007)
In this study we analyzed the ovipositional behavior of C. albiceps, C. megacephala and L. eximia in response to previous presence of larvae of different species, both predator and prey. The preference for substrates that previously had had no larvae was predominant for all species. However, the experiments showed that C. megacephala and L. eximia avoid laying eggs principally in patches with previous presence of C. albiceps larvae. The implications of these results for the necrophagous Diptera community dynamics are discussed.
Keywords: oviposition; population dynamics; blowflies